A New Sediment Accumulation Model of Cenozoic Depositional Ages From the Qaidam Basin, Tibetan Plateau. Issue 11 (28th November 2018) - Cheng, Feng; Garzione, Carmala; Jolivet, Marc; Guo, Zhaojie; Zhang, Daowei; Zhang, Changhao
Abstract: Two debated age models, with a basal age of ~50 Ma versus ~30 Ma, are proposed for the depositional age of Cenozoic strata within the Qaidam basin result in a diverse understanding of the initial pattern of deformation in the northern Tibetan Plateau. To evaluate these age models, we integrated isopach maps within the basin with published thermochronology data from surrounding ranges to balance the sediments preserved in the basin with materials eroded in the drainage area. When following the traditional ~50 Ma age model, the total volume of material eroded from the surrounding source area is 4.4 ± 0.3 × 10 5  km 3 . Using instead the ~30 Ma age model for the basal Lulehe Formation and related revisions to the basin chronology, the volume of eroded material is calculated at 3.5 ± 0.2 × 10 5  km 3, which provides a better match to the calculated total volume of solid grains that are preserved in the basin (2.8 ± 0.1 × 10 5  km 3 ). However, growth strata revealed in seismic profiles along the Southern Qaidam Thrust suggest reverse‐faulting began during the deposition of Oligocene‐Miocene strata. Following the ~50 Ma age model, the onset time of faulting along the Southern Qaidam Thrust is ~35.5 Ma, consistent with previous thermochronology results. If both age models are correct, then this requires a significant time‐transgressive nature to basin fill that allows for older ages of deposition in the southern part of the basin. This study highlights the need for further effort to determine the depositional age of the strata in the southern and western parts of the Qaidam basin. Key Points: We balance the sediment volume preserved in the Qaidam basin with material eroded in the surrounding ranges We tested two competing models of basin fill and erosion commencing 30 and 50 Ma Our analysis is consistent with both the 30 and 50 Ma ages suggesting time‐transgressive basin fill